Violence Against Children : Prevention and Response - World Bank (World Bank, Washington, DC, 2020)
Uganda is the largest refugee-hosting country in Africa and the third-largest worldwide. Because of ongoing conflicts and instability in the Democratic Republic of Congo and South Sudan, Uganda is hosting over 1.33 million refugees and asylum seekers. The prolonged and steady influx of refugees has far-reaching implications. Refugee-hosting areas are among the poorest and least-developed areas in the country. Women and children comprise eight-two percent of Uganda’s overall refugee population. The country is likely to continue experiencing an influx of refugees as it continues to implement its open-door policy. This note provides practical guidance on how to effectively identify, assess, and manage the risk of violence against children (VAC) in a context of a development response to forced displacement. It is intended to help government and non-government actors involved in the design, implementation, monitoring, and evaluation of the Uganda Development Response to Displacement Impacts Project (DRDIP) ensure that there are effective mechanisms in place for the identification and response to risk of VAC.